The importance of 5S implementation to the government sector at Majlis Perbandaran Kuantan (MPK) Pahang / Nurliyana Najwa Jamaludin - Jamaludin, Nurliyana Najwa (Faculty of Business And Management, 2013)
The study investigated the importance of 5S implementation to the government sector at Majlis Perbandaran Kuantan (MPK). This study contained independent variables with the impact of 5S implementation towards government staffs at the assigned place. This paper examined how these factors influenced productivity, quality and performance of the staff. The research was carried out in Majlis Perbandaran Kuantan, Pahang (MPK). The population of this research was 300 staffs, about 100.10 of staffs had chosen through the application of a sampling technique. It used simple random sampling technique to collect all the data. The main data collection method for this research was questionnaires. All the data were entered and processed into by used IBM Statistical Package for Social Science 20 version program (SPSS). The finding showed 5S gave good impacts to the Majlis Perbandaran Kuantan (MPK) staffs.